A super ionic liquid-rich microporous nanofiber electrode material and its preparation method and application

The superionic liquid microporous nanofiber electrode material prepared by ultrasonic dispersing carbon nanotubes and by phenolic condensation and carbonization activation processes solves the problems of low compaction density and poor electrochemical performance of composite carbon nanofiber electrode materials, and achieves high compaction density and excellent electrochemical performance.

CN115206687BActive Publication Date: 2025-02-28WUHAN UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202210838934.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-07-18
Publication Date
2025-02-28
Estimated Expiration
2042-07-18

AI Technical Summary

Technical Problem

When existing composite carbon nanofibers are used as electrode materials in supercapacitors, their compaction density is low and their electrochemical performance is poor.

Method used

Ultrasonic dispersed carbon nanotubes were used to prepare ultra-ionic liquid rich microporous nanofiber electrode materials through phenolic condensation and carbonization activation processes. This material uses carbon nanotubes as the conductive core and microporous carbon as the capacitor shell. It forms a dense 3D skeleton through carbonization and activation to improve compaction density.

Benefits of technology

High compaction density and excellent electrochemical performance are achieved, and high specific capacitance, high specific energy density, excellent rate performance and stable cycling performance are shown.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

The present invention discloses a super ionic liquid rich microporous nanofiber electrode material and a preparation method and application thereof. The preparation method comprises the steps of: ultrasonically dispersing carbon nanotubes in deionized water, adding a phenol source, stirring and dissolving, and then adding an aldehyde source for phenolic condensation, filtering and washing to obtain graphite carbon@phenolic resin nanofibers with a core-shell structure; carbonizing under an inert atmosphere to obtain graphite carbon@amorphous carbon nanofibers; under an inert atmosphere, mixing graphite carbon@amorphous carbon nanofibers and an activator, carbonizing and activating to obtain a super ionic liquid rich microporous nanofiber electrode material. The electrode material provided by the present invention has conductive inner core carbon nanotubes and in-situ doped nitrogen atoms that synergistically improve the conductivity and electrochemical properties of the material, and the microporous carbon fiber has a super ionic liquid surface, which exhibits high specific capacitance, high specific energy density, excellent rate performance and cycle stability when used as a supercapacitor electrode material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electrochemical energy storage, and in particular to a super ionophilic liquid microporous nanofiber electrode material and a preparation method and application thereof. Background Art

[0002] In order to adapt to the development of modern intelligent electronic devices, it is urgent to design supercapacitors with both high specific energy density and high specific power density. As a member of the carbon family, one-dimensional carbon nanotubes have high mechanical strength and excellent conductivity. They can achieve fast axial electron transmission in supercapacitors and show high frequency response. However, their specific surface area is generally less than 1000m 2 g -1 , and are rarely used simply as capacitor electrode materials. At the same time, the surface of one-dimensional carbon nanofibers has abundant defect active sites, which can achieve rapid radial ion diffusion in supercapacitors and show excellent electrode / electrolyte interface wettability. Therefore, the prior art mostly uses a composite structure of carbon nanotubes @ carbon nanofibers to meet efficient electron-ion dual conduction during the charging and discharging process. However, carbon nanofibers used as supercapacitor electrode materials generally have the problem of low compaction density.

[0003] At present, carbon nanofibers are mainly obtained by template method and electrospinning method. Professor Yu Chengzhong's research group (Small2019,1904310) used resorcinol and formaldehyde as carbon sources and tetraethyl silicate as silicon source to co-assemble composite carbon nanofibers on carbon nanotubes, in which the silicon template needs to be removed by subsequent etching. Professor Zhou Liang's research group (Sci.Bull.2019,64,1617-1624) used hexadecyltrimethylammonium bromide as a soft template and inducer to obtain carbon nanofibers by hydrothermal reaction at 85°C. In 6M KOH electrolyte, the specific capacitance is 380F g at a current density of 1A g-1. -1 , the energy density is 12.4Wh kg -1 , power density is 130W kg -1 However, both the soft template method and the hard template method involve the cost of preparing and removing the template, and the process is cumbersome, time-consuming and labor-intensive. Professor Lou Xiongwen's research group (Energy Environ. Sci., 2017, 10, 1777--1783) obtained porous carbon nanofibers by electrospinning imidazole molecular sieves embedded in polyacrylonitrile. In a 2M H2SO4 electrolyte, 1A g -1 The specific capacity at the current density is 307F g -1 , the energy density is 10.96W h kg -1 , power density is 25000W kg -1However, its synthesis is complex, spinning efficiency is low, cost is high, and pollution is high, making it unsuitable for large-scale promotion.

[0004] Based on this, it is of great significance to design and synthesize composite carbon nanofiber electrode materials that have simple synthesis strategies, high compaction density and high electrochemical performance. Summary of the invention

[0005] In view of this, the present invention provides a super ionic liquid rich microporous nanofiber electrode material and a preparation method and application thereof, so as to solve the problems of low compaction density and poor electrochemical performance of existing composite carbon nanofiber electrodes.

[0006] To achieve the above object, the technical solution of the present invention is achieved as follows:

[0007] A method for preparing a super ionic liquid-rich microporous nanofiber electrode material comprises the following steps:

[0008] S1, ultrasonically dispersing carbon nanotubes in deionized water, adding a phenol source, stirring and dissolving, and then adding an aldehyde source for phenolic condensation, and obtaining graphite carbon@phenolic resin nanofibers with a core-shell structure after filtration and washing;

[0009] S2. In an inert atmosphere, carbonizing the graphite carbon@phenolic resin nanofibers to obtain graphite carbon@amorphous carbon nanofibers;

[0010] S3. In an inert atmosphere, the graphite carbon@amorphous carbon nanofibers and an activator are mixed and carbonized and activated to obtain a super ionic liquid-rich microporous nanofiber electrode material.

[0011] According to the above scheme, in step S1, the mass ratio of the carbon nanotubes, the phenol source and the aldehyde source is (0.005-0.05):1:1.5.

[0012] According to the above scheme, the phenol source includes one of m-aminophenol, o-aminophenol and p-aminophenol, and the aldehyde source includes formaldehyde or acetaldehyde.

[0013] According to the above scheme, in step S1, the reaction temperature of the phenol-formaldehyde condensation reaction is 20-100° C., and the reaction time is 10-60 min.

[0014] According to the above scheme, in step S2, the carbonization conditions include: 500-1400°C, carbonization time 100-200min, heating rate 2-10°C min -1 .

[0015] According to the above scheme, in step S3, the mass ratio of the carbon nanofibers to the activator is in the range of 1:2 to 1:5.

[0016] According to the above scheme, the activator includes potassium hydroxide or potassium bicarbonate.

[0017] According to the above scheme, in step S3, the carbonization activation conditions include: activation temperature of 700-800°C, time of 60-180 min, heating rate of 2-5°C min -1 .

[0018] On the basis of the above scheme, the second purpose of the present invention is to provide a super ionic liquid rich microporous nanofiber electrode material, which is prepared by the above-mentioned method for preparing the super ionic liquid rich microporous nanofiber electrode material.

[0019] On the basis of the above scheme, the third object of the present invention is to provide the application of the above-mentioned super ionic liquid rich microporous nanofiber electrode material as a supercapacitor active material.

[0020] Compared with the prior art, the present invention has the following advantages:

[0021] (1) The super-ionic liquid-rich microporous nanofiber electrode material of the present invention has a dense 3D skeleton and a high compaction density. It uses carbon nanotubes as a conductive core and microporous carbon as a capacitor shell, which can achieve rapid electron-ion dual conduction. At the same time, the microporous carbon fiber has a super-ionic liquid surface with a contact angle of almost zero, and the micropore size is slightly larger than the ion size in the ionic liquid electrolyte. When used as a supercapacitor electrode material, it exhibits high specific capacitance, high specific energy density, excellent rate performance and cycle stability.

[0022] (2) The preparation method provided by the present invention is simple to operate, short in preparation time, low in cost, and has a simple and green synthesis process without the need to remove the template. In addition, the reaction is carried out in a pure water system without the addition of an organic solvent, and is suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0024] Figure 1 This is a diagram showing the synthesis mechanism of the super ionic liquid-rich microporous nanofiber electrode material of the present invention;

[0025] Figure 2The SEM image (a) and TEM image (b, c) of the core-shell structured graphite carbon@phenolic resin nanofibers described in Example 1 of the present invention, the SEM image (d) and TEM image (e, f) of the core-shell structured graphite carbon@amorphous nitrogen-doped carbon nanofibers, the SEM image (g), TEM image (h, i) and EDS spectrum (j) of the super ionic liquid-rich microporous nanofibers;

[0026] Figure 3 XRD patterns of the nitrogen-doped porous carbon materials described in Examples 1, 2 and 3 of the present invention;

[0027] Figure 4 The Raman spectra of the nitrogen-doped porous carbon materials described in Examples 1, 2 and 3 of the present invention;

[0028] Figure 5 The adsorption-desorption curve and pore size distribution curve of the nitrogen-doped porous carbon material described in Examples 1, 2 and 3 of the present invention;

[0029] Figure 6 The XPS spectrum of the super ionic liquid microporous nanofiber electrode material described in Example 1 of the present invention;

[0030] Figure 7 This is a wettability test diagram of the nitrogen-doped porous carbon material described in Examples 1, 2 and 3 of the present invention;

[0031] Figure 8 The cyclic voltammetry curve of the super ionic liquid-rich microporous nanofiber electrode material described in Example 1 of the present invention;

[0032] Fig. 9 The cyclic voltammetry curves of the nitrogen-doped porous carbon materials described in Examples 1, 2 and 3 of the present invention;

[0033] Fig.10 This is a charge and discharge curve diagram of the super ionic liquid-rich microporous nanofiber electrode material at different current densities described in Example 1 of the present invention;

[0034] Fig.11 The rate curves of the nitrogen-doped porous carbon materials described in Examples 1, 2 and 3 of the present invention;

[0035] Fig.12 This is the cycle curve of the super ionic liquid-rich microporous nanofiber electrode material described in Example 1 of the present invention;

[0036] Fig.13 The SEM images (a, d) of the phenolic resin microspheres described in Example 3 of the present invention, the SEM images (b, e) of the nitrogen-doped carbon microspheres, and the SEM images (c, f) of the microporous nitrogen-doped carbon microspheres;

[0037] Fig.14This is a charge and discharge curve diagram of the carbon nanotubes after carbonization and activation described in Example 4 of the present invention. DETAILED DESCRIPTION

[0038] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, specific embodiments of the present invention are described in detail below with reference to the accompanying drawings.

[0039] It should be noted that in the description of the embodiments of the present application, the description of the term "some specific embodiments" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same implementation or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0040] In this embodiment, “in the range of…” includes both end values, such as “in the range of 1 to 100” includes both end values ​​of 1 and 100.

[0041] The present invention provides a method for preparing a super ionic liquid-rich microporous nanofiber electrode material, comprising the following steps:

[0042] S1. In a pure water system, carbon nanotubes are ultrasonically dispersed in deionized water, a small amount of phenol source is added, stirred and dissolved, and then an aldehyde source is added for phenolic condensation, and gray core-shell graphite carbon@phenolic resin nanofibers are obtained after filtration and washing;

[0043] S2. In an inert atmosphere, the core-shell graphite carbon@phenolic resin nanofibers are carbonized in one step to obtain black core-shell graphite carbon@amorphous carbon nanofibers;

[0044] S3. In an inert atmosphere, the black core-shell graphite carbon@amorphous carbon nanofibers and an activator are mixed and carbonized and activated to obtain black core-shell graphite carbon@microporous carbon nanofibers, i.e., super ionic liquid microporous nanofiber electrode materials.

[0045] Combination Figure 1 As shown, the synthesis mechanism of super ionic liquid rich microporous nanofiber electrode material is as follows: carbon nanotubes modified with surface oxygen functional groups can be uniformly dispersed in aqueous solution due to hydrogen bonding. When m-aminophenol and formaldehyde are added, the uniformly dispersed carbon nanotubes modified with surface oxygen functional groups can effectively reduce the nucleation barrier of phenolic condensation as heterogeneous nucleation sites. Under the action of hydrogen bonding, core-shell structured graphite carbon@phenolic resin nanofibers are grown along the surface of carbon nanotubes. Since the fiber surface is rich in amino and hydroxyl functional groups, it is dominated by hydrogen bonding forces during the carbonization process, and the three-dimensional fiber framework is compressed and becomes dense. Finally, the compressed rich microporous three-dimensional carbon framework nanofiber electrode material can be obtained after activation.

[0046] Specifically, in step S1, the mass ratio of carbon nanotubes, phenol source and aldehyde source is (0.005-0.05):1:1.5. The phenol source includes one of m-aminophenol, o-aminophenol and p-aminophenol, and the aldehyde source includes formaldehyde or acetaldehyde. Further, the phenol source is preferably m-aminophenol, and the aldehyde source is preferably formaldehyde.

[0047] In order to improve the reaction efficiency, the reaction temperature of the phenol-formaldehyde condensation reaction is 20-100° C., and the reaction time is 10-60 min.

[0048] The core-shell structure is a microporous nanostructure with a greatly increased specific surface area, which improves the wettability between the electrolyte and the electrode material; in addition, the core-shell structure forms a three-dimensional interwoven network structure, which is beneficial to the rapid transmission of electrons and ions inside the electrode material during the redox process, further improving the specific capacitance of the electrode material.

[0049] Specifically, in step S2, the one-step carbonization conditions include: 500-1400°C, carbonization time 100-200 min, heating rate 2-10°C min -1 Preferably, the carbonization temperature is 800°C, the carbonization time is 120 min, and the heating rate is 2°C min -1 .

[0050] Doping with nitrogen can increase the active sites and show better performance. The conductive core carbon nanotubes and in-situ doped nitrogen atoms synergistically improve the conductivity and electrochemical properties of the material.

[0051] In step S3, the mass ratio of the carbon nanofibers to the activator is in the range of 1:2 to 1:5, wherein the activator is preferably potassium hydroxide.

[0052] Furthermore, the conditions for carbonization activation include: activation temperature of 700-800°C, time of 60-180 min, heating rate of 2-5°C min -1 Preferably, the activation temperature is 750°C, the time is 120 min, and the heating rate is 3°C min -1 .

[0053] Therefore, the preparation process provided by the present invention is simple and green, does not need to remove the template, and has low cost; in addition, the reaction is carried out in a pure water system without the addition of an organic solvent, and is suitable for industrial production.

[0054] Based on the above scheme, another embodiment of the present invention provides a super ionic liquid-rich microporous nanofiber electrode material, which is prepared by the above-mentioned method for preparing the super ionic liquid-rich microporous nanofiber electrode material.

[0055] Based on the above solution, another embodiment of the present invention provides the use of the above super ionic liquid rich microporous nanofiber electrode material as a supercapacitor active material.

[0056] The super ionophilic liquid microporous nanofiber electrode material provided by the present invention has a dense 3D skeleton and high compaction density. It uses carbon nanotubes as a conductive core and microporous carbon as a capacitor shell. The conductive core carbon nanotubes and in-situ doped nitrogen atoms synergistically improve the conductivity and electrochemical properties of the material, and can achieve rapid electron-ion dual conduction. At the same time, the microporous carbon fiber has developed micropores and mesopores, and the micropore size is slightly larger than the ion size in the ionic liquid electrolyte, and the contact angle with the electrolyte is almost zero. It has a super ionophilic liquid surface and exhibits high specific capacitance, high specific energy density, excellent rate performance and stable cycle performance when used as a supercapacitor electrode material.

[0057] On the basis of the above-mentioned embodiments, the present invention provides the following specific examples to further illustrate the present invention. It should be understood that these examples are only used to illustrate the present invention and are not used to limit the scope of the present invention. The experimental methods without specifying specific conditions in the following examples are usually based on the conditions recommended by the manufacturer. Unless otherwise stated, percentages and parts are calculated by mass.

[0058] Example 1

[0059] This embodiment provides a method for preparing a super ionic liquid-rich microporous nanofiber electrode material, comprising the following steps:

[0060] 1) 25 mg of carbon nanotubes were dispersed in 300 mL of deionized water, 2.475 g of m-aminophenol was added to dissolve, and then 3.42 mL of formaldehyde was added to react for 0.5 h. After filtration, washing and drying, gray core-shell graphite carbon@phenolic resin nanofibers (CNT@APF) were obtained;

[0061] 2) The dried CNT@APF was carbonized at 800 °C for 2 h in a nitrogen atmosphere with a heating rate of 2 °C min -1 , black core-shell structured graphite carbon@amorphous nitrogen-doped carbon nanofibers (CNT@NC) were obtained;

[0062] 3) CNT@NC and KOH were mixed in a mass ratio of 1:4 and activated at 750 °C for 1 h in a nitrogen atmosphere with a heating rate of 2 °C min -1 The activated sample was washed with dilute hydrochloric acid to remove impurities and then washed with water until neutral to obtain a super ionic liquid-rich microporous nanofiber electrode material - black core-shell structured graphite carbon @ rich microporous nitrogen-doped carbon nanofiber (CNT@NC-A).

[0063] Example 2

[0064] This embodiment provides a method for preparing a nanofiber electrode material, comprising the following steps:

[0065] 1) 25 mg of carbon nanotubes were dispersed in 300 mL of deionized water, 2.475 g of m-aminophenol was added to dissolve, and then 3.42 mL of formaldehyde was added to react for 0.5 h. After filtration, washing and drying, gray core-shell graphite carbon@phenolic resin nanofibers (CNT@APF) were obtained;

[0066] 2) The dried CNT@APF was carbonized at 800 °C for 2 h in a nitrogen atmosphere with a heating rate of 2 °C min -1 , and obtained black core-shell structured graphite carbon@amorphous nitrogen-doped carbon nanofibers (CNT@NC).

[0067] The difference between the electrode materials prepared in this embodiment and in embodiment 1 is that the core-shell structured graphite carbon@amorphous nitrogen-doped carbon nanofibers in this embodiment are not activated with potassium hydroxide.

[0068] Example 3

[0069] This embodiment provides a method for preparing a nanofiber electrode material, comprising the following steps:

[0070] 1) Add 2.475 g of m-aminophenol to 300 mL of deionized water to dissolve, then add 3.42 mL of formaldehyde to react for 0.5 h, and then filter, wash, and dry to obtain yellow phenolic resin microspheres (APF);

[0071] 2) Carbonize the dried APF at 800℃ for 2h in a nitrogen atmosphere with a heating rate of 2℃min -1 , black nitrogen-doped carbon microspheres (NCS) were obtained;

[0072] 3) Mix NCS and KOH in a mass ratio of 1:4 and activate at 750 °C for 1 h in a nitrogen atmosphere with a heating rate of 2 °C min -1 The activated sample was washed with dilute hydrochloric acid to remove impurities and then washed with water until neutral to obtain black microporous nitrogen-doped carbon microspheres (NCS-A).

[0073] Taking the super ionic liquid-rich microporous nanofiber electrode material prepared in Example 1 as an example, the morphology and structure of CNT@APF, CNT@NC and CNT@NC-A were characterized to obtain Figure 2-7 The result graph is shown.

[0074] Figure 2 SEM images (a) and TEM images (b, c) of CNT@APF, SEM images (d) and TEM images (e, f) of CNT@NC, SEM images (g), TEM images (h, i) and EDS energy spectrum (j) of CNT@NC-A. Figure 2 It can be seen that the synthesized graphite carbon@phenolic resin nanofiber CNT@APF is in a state of cross-linking, the fiber size is about 60nm, the core layer carbon nanotube diameter is 5-10nm, and the three-dimensional network is loose and has large pores. During the carbonization process, adjacent fibers approach each other under the action of hydrogen bonds, reducing the proportion of useless cavities, increasing the network density, and slightly reducing the fiber diameter. After activation treatment, due to the excellent thermal stability and etching resistance of phenolic resin-based carbon, the fiber diameter does not change much, but a rich microporous structure is formed inside the fiber. The C and O elements are evenly distributed on the fiber, while the N element is relatively less distributed at the carbon nanotubes, reflecting the distribution of carbon nanotubes in the fiber.

[0075] To further illustrate the effect of adding carbon nanotubes on super ionic liquid-rich microporous nanofiber electrode materials, the data in Table 1 were obtained by comparing the synthesis yield, carbonization yield and activation yield of porous carbon spheres and porous carbon fibers.

[0076] Table 1 Nitrogen doped porous carbon material yield

[0077]

[0078] As can be seen from Table 1, compared with the sample without carbon nanotubes, the addition of trace carbon nanotubes not only increases the conductivity of the material, induces the transformation of resin nucleation growth from three-dimensional to one-dimensional, but also improves the yield of the precursor, increases the thermal stability and etching resistance of the resin material, and the final product yield of porous carbon fiber (CNT@NC-A) is increased by 43.1% under the same conditions compared with porous carbon spheres (NCS-A).

[0079] Figure 3 XRD diagram of nitrogen-doped porous carbon materials described in Examples 1, 2 and 3. Figure 3 It can be seen that the two large peaks at 24° and 43° of CNT@NC-A prepared in Example 1, CNT@NC prepared in Example 2, and NCS-A prepared in Example 3 correspond to the diffraction of amorphous carbon at (002) and (100) crystal planes, indicating their amorphous structures. Compared with CNT@NC, the diffraction peak intensity of NCS-A and CNT@NC-A after activation treatment is weakened.

[0080] Figure 4 The Raman graphs of the nitrogen-doped porous carbon materials described in Examples 1, 2 and 3 are shown in Table 1. Figure 4 It can be seen that the CNT@NC-A prepared in Example 1 and the CNT@NC prepared in Example 2 have a -1 and 1580cm -1 The peaks at 2700 cm-1 correspond to the typical amorphous peaks and graphitization peaks of carbon materials. The G peak has a high intensity due to the presence of carbon nanotubes. -1There is a typical 2D peak at 1360 cm -1 and 1580cm -1 The peaks at the bottom correspond to the typical amorphous peak (D peak) and graphitization (G peak) of carbon materials. Due to the absence of carbon nanotubes, the ratio of the D peak to the G peak is about 1, indicating that the activated material has a certain degree of graphitization while maintaining an amorphous structure.

[0081] Figure 5 The adsorption-desorption curves and pore size distribution curves of the nitrogen-doped porous carbon materials described in Examples 1, 2 and 3 are shown in FIG. Figure 5 It can be seen that the specific surface area of ​​the CNT@NC-A material prepared in Example 1 reaches 2059 m2g -1 The micropore volume is 0.69cm3g -1 , with abundant micropores and mesoporous structures, and the micropore size is slightly larger than the ion size in the ionic liquid electrolyte, and all pores are effective pores accessible to ions. The specific surface area of ​​the CNT@NC material prepared in Example 2 reaches 358m 2g -1 , the micropore volume is 0.04cm 3g -1 , indicating that it has not been activated and the micropores are not well developed. The specific surface area of ​​the NCS-A material prepared in Example 3 reaches 770m2g -1 , the micropore volume is 0.24cm3g -1 , with abundant micropores.

[0082] Figure 6 The XPS spectrum of the super ionic liquid rich microporous nanofiber electrode material CNT@NC-A prepared in Example 1 is as follows: Figure 6 It can be seen that the CNT@NC-A material is composed of C (91.80 at.%), N (3.24 at.%) and O (4.96 at.%). The high nitrogen content will greatly improve the electrochemical performance. In addition, after peak fitting, the N species mainly exists in the form of pyrrolic nitrogen.

[0083] Figure 7 and Fig. 9 The wettability test graphs of the nitrogen-doped porous carbon materials described in Examples 1, 2 and 3 are cyclic voltammetry curves, respectively. Figure 7 It can be seen that the initial contact angle of the CNT@NC-A material prepared in Example 1 and the electrolyte is 39.6°, and the contact angle is 0° after 4 minutes, which is in a completely wetted state. Good interface wettability will greatly facilitate the electrochemical performance. The initial contact angle of the CNT@NC material prepared in Example 2 and the electrolyte is 59.9°, and the contact angle does not change much after 4 minutes, indicating that the electrode material of this example is essentially wettable with the electrolyte, but due to the underdeveloped micropores and limited wettability, it exhibits less than ideal capacitance performance (see Appendix). Fig. 9 The initial contact angle of the NCS-A material prepared in Example 3 when in contact with the electrolyte was 85.3°, and the contact angle was 58.0° after 4 minutes, indicating that the electrode material of this example is essentially wettable with the electrolyte, but because the spherical structure is inferior to the three-dimensional network structure in terms of electrolyte wettability, and the specific surface area is less than that of Example 1, the capacitance performance is inferior to that of Example 1 (see Appendix). Fig. 9 ).

[0084] The application of the super ionic liquid rich microporous carbon nanofiber electrode material prepared in Example 1 as a supercapacitor electrode material is as follows: the production process of the electrode sheet uses super ionic liquid rich microporous carbon nanofiber as the active material, acetylene black as the conductive agent, and PTFE as the binder. The three are mixed in a mortar at a mass ratio of 8:1:1, and rolled into an electrode sheet. The ionic liquid EMIMBF4 is used as the electrolyte, and a cellulose diaphragm is used to assemble it into a button cell. Similarly, the electrode materials prepared in Examples 2 and 3 are also assembled into batteries. Electrochemical tests were performed on the assembled button cells, and the results were obtained. Figure 8-12 The result graph is shown.

[0085] Figure 8 The cyclic voltammetry curve of the super ionic liquid rich microporous nanofiber electrode material CNT@NC-A prepared in Example 1 is shown in FIG. Figure 8 It can be seen that the superionic liquid-rich microporous carbon nanofibers exhibit a rectangular shape at different scan rates, indicating their electrochemical capacitive behavior.

[0086] Fig. 9 The cyclic voltammetry curves of the nitrogen-doped porous carbon materials described in Examples 1, 2 and 3 are shown in FIG. Fig. 9 It can be seen from the area of ​​the cyclic voltammetry curve that the capacitance of the battery assembled with CNT@NC-A prepared in Example 1 is much higher than the capacitance of the battery assembled with CNT@NC prepared in Example 2 which is activated, and higher than the capacitance of the battery assembled with NCS-A prepared in Example 3 without adding carbon nanotubes.

[0087] Fig.10 , 12 The charge-discharge curves and cycle curves of the super ionic liquid-rich microporous nanofiber electrode material CNT@NC-A prepared in Example 1 at different current densities are shown in FIG. Fig.10 It can be seen that at 1A g -1 At current densities as high as 219 F g -1 The specific capacitance at 10A g -1 At a current density of 1.5 20000 cycles, the capacity retention rate is as high as 95% (see Appendix Fig.12), which is due to the good wettability of the electrode / electrolyte interface. According to further conversion, its energy density is 108.8Wh kg -1 , the power density can reach 946.3W kg -1 .

[0088] Fig.11 is the rate curve of the nitrogen-doped porous carbon material described in Examples 1, 2 and 3, from Fig.11 It can be seen that the CNT@NC-A battery prepared in Example 1 has a -1 The specific capacitance is still as high as 160F g at the current density -1 , which is much higher than the CNT@NC battery prepared in Example 2 and the NCS-A battery prepared in Example 3. The excellent rate performance is due to nitrogen doping and the efficient electron-ion dual conduction effect of the structure.

[0089] Fig.13 The SEM images (a, d) of the phenolic resin microspheres APF described in Example 3, the SEM images (b, e) of the nitrogen-doped carbon microspheres NCS, and the SEM images (c, f) of the microporous nitrogen-doped carbon microspheres NCS-A. Fig.13 It can be seen that the phenolic resin microspheres are monodisperse spheres with a diameter of 600nm. During the carbonization process, small molecule precursors escape and the resin shrinks to obtain monodisperse carbon microspheres with a diameter of 500nm. The nitrogen-doped carbon microspheres, under the etching action of alkali during the activation process, the microporous nitrogen-doped carbon microspheres maintain a stable monodisperse state with a size of 450nm.

[0090] In summary, the super ionic liquid microporous nanofiber electrode material prepared by the present invention has a microporous carbon fiber size of 40nm and a specific surface area of ​​up to 2059m2 g -1 The surface density of the prepared electrode sheet is 2.6 g cm -2 It exhibits excellent wettability (θ-0°) to ionic liquid electrolytes and exhibits high specific capacitance, high specific energy-power density, excellent rate performance and stable cycle performance as a supercapacitor electrode material.

[0091] Example 4

[0092] This embodiment provides a method for preparing carbon nanotubes, comprising the following steps:

[0093] 100 mg of carbon nanotubes were dispersed in 1200 mL of deionized water, filtered, washed, and dried, and then carbonized at 800 °C for 2 h in a nitrogen atmosphere at a heating rate of 2 °C min -1 Then, it was mixed with KOH in a mass ratio of 1:4 and activated at 750 °C for 1 h in a nitrogen atmosphere with a heating rate of 2 °C min -1The activated sample was washed with dilute hydrochloric acid to remove impurities, and then washed with water until neutral, to obtain black activated carbon nanotubes (CNT-A).

[0094] Fig.14 The charge-discharge curve of carbon nanotube CNT-A after carbonization and activation described in Example 4 is shown in FIG. Fig.14 It can be seen that at 1A g -1 At this current density, the specific capacitance of activated carbon nanotubes is 25.2 F g -1 , showing extremely limited capacitive performance.

[0095] Although the present invention is disclosed as above, the protection scope of the present invention is not limited thereto. Those skilled in the art may make various changes and modifications without departing from the spirit and scope of the present invention, and these changes and modifications will fall within the protection scope of the present invention.

Claims

1. A method for preparing a super ionic liquid-rich microporous nanofiber electrode material, characterized in that: The steps include: S1, ultrasonically dispersing carbon nanotubes in deionized water, adding a phenol source, stirring and dissolving, and then adding an aldehyde source for phenolic condensation, and filtering and washing to obtain graphite carbon@phenolic resin nanofibers with a core-shell structure; S2. In an inert atmosphere, carbonizing the graphite carbon@phenolic resin nanofibers to obtain graphite carbon@amorphous carbon nanofibers; S3, under an inert atmosphere, mixing the graphite carbon@amorphous carbon nanofibers and an activator, and carbonizing and activating them to obtain a super ionic liquid-rich microporous nanofiber electrode material; The phenol source includes one of m-aminophenol, o-aminophenol and p-aminophenol. In step S1, the reaction temperature of the phenol-formaldehyde condensation reaction is 20-100° C., and the reaction time is 10-60 min.

2. The preparation method according to claim 1, characterized in that: In step S1, the mass ratio of the carbon nanotubes, the phenol source and the aldehyde source is (0.005-0.05):1:1.

5.

3. The preparation method according to claim 1 or 2, characterized in that: The aldehyde source includes formaldehyde or acetaldehyde.

4. The preparation method according to claim 1, characterized in that: In step S2, the carbonization conditions include: carbonization temperature 500-1400°C, carbonization time 100-200 min, heating rate 2-10°C min -1 .

5. The preparation method according to claim 1, characterized in that: In step S3, the mass ratio of the carbon nanofibers to the activating agent is in the range of 1:2 to 1:

5.

6. The preparation method according to claim 5, characterized in that: The activator includes potassium hydroxide or potassium bicarbonate.

7. The preparation method according to claim 5, characterized in that: In step S3, the carbonization activation conditions include: activation temperature of 700-800°C, time of 60-180 min, heating rate of 2-5°C min -1 .

8. A super ionic liquid rich microporous nanofiber electrode material, characterized in that: The electrode material is prepared by the method for preparing the super ionic liquid-rich microporous nanofiber electrode material according to any one of claims 1 to 7.

9. Use of the superionic liquid-rich microporous nanofiber electrode material obtained by the preparation method according to any one of claims 1 to 7 or the superionic liquid-rich microporous nanofiber electrode material according to claim 8 as a supercapacitor active material.